Developing a Conceptual Model of Green Supply Chain Antecedents and Consequences using Qualitative Qualification Approach - Navid Pishkar; Mohammad ali Nasimi; Maryam Rahmati (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2020)
The purpose of this study is to develop a conceptual model and classify the antecedents and consequences of the green supply chain in the parts industry. The study method is qualitative content analysis and the main tool for data collection is semi-structured interviews. Data analysis was performed using a combination of directional and summary content analysis techniques. The identified factors include 29 open codes that were inserted in the form of seven main categories and at the end, using Max Kyoda software, classification and conceptual model were drawn. Reliability using kappa coefficient was equal to 0.960, which is at the level of excellent agreement. The results show that the 7 components identified in the antecedents and consequences of the green supply chain in the component manufacturing industry include; Supplier and green purchase, green design and packaging, green production, green distribution and marketing, environmental management, education and research, reverse logistics. The components of education and research and reverse logistics have emerged as new components in this research. Today, in a competitive environment, global organizations have realized that improving environmental performance can set them apart from their competitors